Literature Review: Strategy Analysis of Pharmaceutical Service Quality Improvement - Arie Sulistiyoningrum; Ayun Sriatmi; Septo Pawelas Arso (Universitas Aisyah Pringsewu, 2021)
Hospitals are individual health service facilities and part of health resources that are indispensable in supporting the implementation of health efforts. Quality improvement in health services is not only oriented to quality service processes but also the results of the quality of health services following the wishes of customers or patients. One type of hospital service that must be provided is pharmacy services. Pharmacy services must be carried out according to predetermined service standards. Problems that are still encountered in Indonesian hospital pharmacy installations are: speed of service time is not optimal, service friendliness is still not optimal, and limited drug availability. This study aims to determine the strategy for improving the service quality of hospital pharmacy installations in Indonesia. This research is a literature review by searching electronic databases published in 2017-2022 and meeting the inclusion criteria. Articles were taken from the Scopus, Science Direct, ProQuest, Springer Link, Google Scholar, Nature, JSTOR, and Emerald Insight databases with a total of 20 articles used. Twenty articles show that to improve the service quality of hospital pharmacy installations in Indonesia is to pay attention to several aspects of indicators including, service friendliness, service speed, service accuracy, product completeness, workforce professionalism, and service convenience